Studi of the History and Islamic Civilization of the Archipelago, Case Study: Analysis of Al-Musthofa Mosque Bogor - Muhammad Yusuf Pratama; Ulfa Shofi Rohmawati; Mokh Sya'roni (UIN Imam Bonjol Padang, 2025)
The development of Islam in the Indonesian archipelago remains a significant area of scholarly inquiry. Classical Islamic civilization became a dominant influence on the subsequent evolution of Islam in the region. Islamic civilization developed in various ways, including the construction of mosques by scholars during the classical period. Al-Musthofa Mosque stands as one such historical mosque that played a crucial role in the progression of Islam in Indonesia. The mosque's continued function as a gathering place for Muslim communities, along with the presence of handwritten Qur'anic manuscripts and local historical narratives, attests to the advancement of Islamic civilization in this area. This research aims to examine historical development of Islamic teachings and analyze classical Islamic civilization through the lens of the Al-Musthofa Mosque in Bogor. Employing a qualitative research design, this study utilizes historical analysis as its primary methodological instrument. Primary data were collected through observation and interviews, while the secondary data was obtained using documentation techniques used to collect supporting data. The research findings reveal historical evidence suggesting that Islamic civilization was readily accepted through da'wah approaches, as exemplified by the historical trajectory of Islam's development facilitated by the Al-Musthofa Mosque. This study contributes to the body of knowledge by uncovering historical evidence of Islamic civilization in Indonesia and serves as a valuable reference for future research in Indonesian Islamic history.